Qualitative exploration of a targeted school‐based mindfulness course in England. Issue 2 (27th June 2018) - McGeechan, Grant J.; Richardson, Catherine; Wilson, Lynn; Allan, Keith; Newbury‐Birch, Dorothy
Abstract : Background: Mindfulness‐based training has been shown to provide benefits for adults with numerous conditions such as cancer, chronic pain, and depression. However, less is known about its impact for young people. Early adolescence (typically 10–14 years) is a time fraught with challenges such as cognitive changes, social, and academic pressures in the form of exams, all of which can provoke anxiety. While there is a lack of effectiveness studies, there is growing interest in the potential for school‐based mindfulness programmes to help young people cope with the pressures of modern life. Methods: This study outlines a qualitative exploration of a school‐based targeted mindfulness course. We interviewed 16 young people who had taken part in a 10‐week mindfulness course, and held a focus group with three members of teaching staff who delivered the programme. Interviews and focus groups were analysed using applied thematic analysis. Results: While young people felt that they had to take part, once they started the programme they enjoyed it. Young people felt that they learned a range of coping skills, and it had a positive impact on their behaviour. However, the targeted approach of the intervention could lead to young people being stigmatised by their peers. Teaching staff could see the potential benefit of mindfulness courses in schools but felt there were some barriers to be overcome if it were to be implemented in the long term. Conclusions: Young people were willing to engage in mindful practice and felt it better equipped them to deal with stressful situations.